Critical analysis of the book "Philosophy of Rhetoric" - Mohammadi Rahimi Khoigan; Mohammad Khaqani Isfahani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Critical analysis of written several books on various subjects and fields is an important and necessary rule of the critics. One of the most important areas of research is rhetoric that is still considered by many researchers. It is one of the updated and significant areas of research which attracts the attention of many researchers, so it should be reviewed academically   and orderly research and books that should be reviewed properly. Accordingly, a critical review of the book "Philosophy of Rhetoric" by Raja Eid the full Professor of the University Banha, Egypt, as the main issue of this study is selected. The important findings of this research, which are based on interpretive-critical view, show that the respected author has tried to criticize the old rhetoric and look at them with a new look, but it does not seem that much of this work has been successful in considering logical classifications, philosophical and discursive discussions.